Existing State of Affairs of Ethno-Traditional Pork Processing by the Tribal Pig Farmers of Assam, India - Biju Borah , Atul Borgohain , M. N. Ray , L. Sanathoi Khuman, Bikash Borthakur, Chintu Debbarman; Tasso Konia (Indian Journal of Extension Education, 2017)
A study was carried out in four prominent districts of Assam i.e. Dhemaji, Karbi Anglong, Kamrup and Baksa district where the availability and consumption of pork and its product was very high. Data were collected from a total of 100 respondents through a pre-tested, reliable and valid interview schedule. Majority of the respondents belonged to middle aged group and Schedule Tribe caste. Agriculture & livestock rearing were the primary occupations. The average pig herd size was 4 and reared pig mostly for flesh purpose. The average annual income from piggery sector and gross annual income of the respondents were Rs. 28135 and Rs. 85870 respectively. About 46.00 per cent of the respondents out of 100 respondents processed pork and majority (40 %) of them processed it occasionally. The majority (30.43 %) of the respondents processed pork basically for their own consumption. The mean availability of processed pork was highest in Kamrup followed by Dhemaji. The storage problem, practicing in fewer quantities and costs related to processing, poor marketing system were the major factors which impeded commercialization of processed pork in many areas of Assam.